Study of Large-Scale Aluminium-Doped Zinc Oxide Ceramic Targets Prepared by Slip Casting - Ling-yun Han; Yong-chun Shu (Advances in Materials Science and Engineering)
Aluminium-doped zinc oxide (AZO) ceramic green compacts at a size of 170 × 340 × 17 mm have been prepared by slip casting. An AZO slurry with good fluidity and viscosity was obtained when 1.2 wt% of dispersant was added, which indicates that the slurry prepared with micrometre particles is more suitable for slip casting. The densification and electrical properties of the AZO targets prepared by particles with different sizes were investigated after sintering from 1380 to 1460°C. The results showed that the relative density of the AZO target prepared with 45 nm particles could reach nearly 98% at 1380°C; the resistivity of the AZO target prepared with nanometre particles could be as low as 1.6 × 10−3 Ω·cm at 1400°C; and the average transmittance of the AZO film prepared with nanometre particles could reach a maximum value of 93.73% in the visible region at 250 W. In this study, the correlation between the density, resistivity, and grain growth of AZO ceramic green compacts was studied.